ACTIVITY OF PLANT ESSENTIAL OILS AGAINST OCHRATOXIN A PRODUCING ASPERGILLUS OCHRACEUS - Gull Naz; Aftab Ahmad Anjum; Muhammad Nawaz; Sanaullah Iqbal; Tehreem Ali; Rabia Manzoor (Journal of Animal and Plant Sciences, 2023)
Plant essential oils have been used in traditional medicines since ancient times to combat disease and in agro-food science to preserve food stuff. Antifungal activity of plant essential oils was evaluated using different substrates of varied moisture levels against ochratoxin A (OTA) producing Aspergillus ochraceus. A.ochraceus (n = 3) isolates were processed for antifungal activity of various essential oils including Zingiber officinale, Curcuma longa, Eucalyptus globulus, Syzygium aromaticum, Nigella sativa, Elettaria cardamomum, Cinnamomum verum and Cuminum cyminum extracted by hydro-distillation. To check the antimicrobial activity of essential oils, the highest zone of inhibition recorded was of C. verum (33.67±0.57mm) followed by S. aromaticum(30.33±0.57mm) and the least minimum inhibitory concentration (MIC) was of S. aromaticum (0.52±0.22 µg/mL) followed by C. verum (0.65±0.22 µg/mL). Antifungal activity was evaluated in term of log reduction and at the exposure time of 60 and 90 min, 6±0.00 log reduction was observed by S. aromaticum, C. verum and E. cardamomum with non-significant differences. At 15th, 30th, 45th and 60th day of experiment, toxin production by A. ochraceus at moisture contents (10, 20, 30, 40, 50, 60 and 70%) in un-inoculated groups and inoculated treated groups with C. verum Essential Oils were found non-significantly different to each other but significantly different from the OTA production in inoculated groups of wheat, maize and rice (intact and broken). At 10% moisture level, OTA production was low and reached to maximum level at 40% moisture level and again decline with increasing moisture level. Cinnamon has showed antifungal activity against A. ochraceus at all moisture levels. The confirmation of inhibition potential of C. verum was evaluated using thin layer chromatography (TLC) and high-performance liquid chromatography (HPLC) techniques. This study illustrates that cinnamon oil is effective to inhibit the growth of OTA producing A. ochraceus in stored grains to overcome the economic losses.
Keywords: Antifungal activity; Cinnamomum verum; Dimethyl sulfoxide; Log reduction; Minimum inhibitory concentration